Diversity of sulfated polysaccharides from cell walls of Coenocytic green algae and their structural relationships in view of green algal evolution - Ciancia, Marina (2020)
Fil: Ciancia, Marina. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Biología Aplicada y Alimentos. Cátedra de Química de Biomoléculas. Buenos Aires, Argentina.